TEACHING ENGLISH TO KID AT HOME - Yuliawati, Fitrah (WACANA DIDAKTIKA, 2015)
Children learn naturally when they are having fun. Children feel more comfortable and confident when they know what to expect. Repetition is essential children often need to hear words and phrases many times before they feel ready to produce them themselves. Established a routine for your English time at hom, it is better to have short, frequent sessions than long, infrequent ones. Fifteen minutes is enough for very young children. Parents can gradually make sessions longer as child gets older and their concentration span increases. Parents have to enthusiastic and give children lots of encouragement andpraise. Children will pick up on enthusiasm for the language. Whatever parents approach, the most important thing is to relax, have fun and make English an enjoyable experience for both parents and child. Many parents are eager to help their kids learn English from a young age. One of the most important factors in teaching foreign languages to young children is helping them form positive perceptions of communicating with foreign languages.A great advantage of early childhood second language exposure is that it helps children form a positive impression of foreign languages. When children are exposed to a foreign language from a very young age, they tend to view the language positively andlearning another language becomes something they are very comfortable with. However, if you force a young child to speak a second language even when they are resisting, you run the risk of creating a negative impression of that language.